Cardiovascular effects of linalyl acetate in acute nicotine exposure - Ju Ri Kim; Purum Kang; Hui Su Lee; Ka Young Kim; Geun Hee Seol (Komiyama Printing Co. Ltd, 2017)
Abstract Backgroud Smoking is a risk factor for cardiovascular diseases as well as pulmonary dysfunction. In particular, adolescent smoking has been reported to have a higher latent risk for cardiovascular disease. Despite the risk to and vulnerability of adolescents to smoking, the mechanisms underlying the effects of acute nicotine exposure on adolescents remain unknown. This study therefore evaluated the mechanism underlying the effects of linalyl acetate on cardiovascular changes in adolescent rats with acute nicotine exposure. Methods Parameters analyzed included heart rate (HR), systolic blood pressure, lactate dehydrogenase (LDH) activity, vascular contractility, and nitric oxide levels. Results Compared with nicotine alone, those treated with nicotine plus 10 mg/kg (p = 0.036) and 100 mg/kg (p = 0.023) linalyl acetate showed significant reductions in HR. Moreover, the addition of 1 mg/kg (p = 0.011), 10 mg/kg (p = 0.010), and 100 mg/kg (p = 0.011) linalyl acetate to nicotine resulted in significantly lower LDH activity. Nicotine also showed a slight relaxation effect, followed by a sustained recontraction phase, whereas nicotine plus linalyl acetate or nifedipine showed a constant relaxation effect on contraction of mouse aorta (p < 0.001). Furthermore, nicotine-induced increases in nitrite levels were decreased by treatment with linalyl acetate (p < 0.001). Conclusions Taken together, our findings suggest that linalyl acetate treatment resulted in recovery of cell damage and cardiovascular changes caused by acute nicotine-induced cardiovascular disruption. Our evaluation of the influence of acute nicotine provides potential insights into the effects of environmental tobacco smoke and suggests linalyl acetate as an available mitigating agent.